1998
DOI: 10.1074/jbc.273.35.22498
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone-Receptor Interactions Identified Directly by Photocross-linking and Molecular Modeling Studies

Abstract: Direct mapping of the interface between parathyroid hormone (PTH) and its receptor (hPTH1-Rc Parathyroid hormone (PTH)1 is the major regulator of calcium levels in blood and plays a role in the regulation of bone remodeling (1). Given intermittently, PTH displays anabolic activity in bone and, therefore, has considerable therapeutic potential (2). PTH and PTH-related protein exert their actions via a seven-transmembrane (TM) domain-containing receptor (PTH1-Rc) (3) belonging to a subfamily of related G protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
277
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 178 publications
(306 citation statements)
references
References 48 publications
28
277
1
Order By: Relevance
“…Many photoaffinity crosslinking reports (including studies from us and others working on different ligand-receptor systems) which identified methionine as the crosslinked residue [1,3,15,16], may now warrant interpretation in a new light. The identified sites of interaction might have been significantly shifted by the presence of methionine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many photoaffinity crosslinking reports (including studies from us and others working on different ligand-receptor systems) which identified methionine as the crosslinked residue [1,3,15,16], may now warrant interpretation in a new light. The identified sites of interaction might have been significantly shifted by the presence of methionine.…”
Section: Discussionmentioning
confidence: 99%
“…Peptide synthesis was carried out as described [1]. Cyanogen bromide (CNBr) was from Aldrich (Milwaukee, WI), Na 125 I from Amersham-Pharmacia (Arlington Heights, IL), and endoglycosidase F/N-glycosidase F (Endo-F) from New England BioLabs (Beverly, MA).…”
Section: Methodsmentioning
confidence: 99%
“…We initially focused our attention on residues in the upper region of TM6 since our previous finding, using Bpa1-PTH, showed that M425 appeared to be a contact point for position 1 of the peptide (6). While investigating this region of TM6, ongoing work in our laboratory suggested that, upon activation of the receptor, the upper regions of TM5 and TM6 move closer together (unpublished data).…”
Section: Identification Of Residues In Tm5 In Close Proximity To Posimentioning
confidence: 99%
“…The Ser1 residue used in the simulations adopts a position equidistant between the extracellular portion of TM5 and TM6, consistent with the general mode of GPCR activation by ligand. (4)(5)(6)8,9,12). By combining data collected from extensive photoaffinity cross-linking studies with molecular modeling, a model of the PTH-PTHR1 bimolecular complex has been generated that identifies regions of contact at the interface between the hormone and the receptor.…”
mentioning
confidence: 99%
See 1 more Smart Citation